Educational Research Review From Diverse Perspectives: A Bibliometric Analysis of Web of Science (2011–2020) - Aslıhan Sezgin; Keziban Orbay; Metin Orbay (SAGE Open, 2022)
This study aims to reveal the bibliometric characteristics of publications on educational research from diverse perspectives, including the level of national-international collaborations, the percentage change in open-access papers, and interactions with other disciplines. Through bibliometric analysis, the data were collected from Web of Science (WoS), “Education and Educational Research (E&ER),”“Psychology, Educational (PE),”“Education, Special (ES)” and “Education Scientific Disciplines (ESD)” categories, during 2011 to 2020. The findings suggest that the number of publications in each category and the percentage of open-access publications have increased regularly. However, it was observed that categories, especially the ES category, were partially falling behind, as compared to the growth in WoS; while the ES and the PE categories were the highest regarding national-international collaborations over time. Both collaboration levels were the highest in the E&ER category. It was concluded that the multi-authorship trend has rapidly increased, the number of references has regularly increased, and specifically, the PE category has been distinguished from others in terms of the references used. Meanwhile, the change over time in the aggregate impact factor, calculated for each category as a measure of the widespread impact of the studies, pointed to inflation. The results show that educational research is becoming more organized and international, while less fragmented. Moreover, the findings support that educational research is interdisciplinary in essence and diverse in content.